A framework on the implementation of sustainable tourism development in the Philippine tourism industry - Rillon, Ruth Maureen C. (Animo Repository, 2012)
The current trend in the global tourism industry is towards sustainable tourism development. The enactment of the Tourism Act of 2009 is a result of the need for a national policy on tourism in order to maximize the potential of the tourism industry (HOR, 2008). This research aims to prove that the effective adaptation and implementation of a Sustainable Tourism Development national framework for the Philippine tourism, which will be measured through a set of selected indicators, will contribute to the socioeconomic development and poverty reduction as well as to the preservation of the natural environment and cultural heritage of the Philippines. A set of indicators will be successful in monitoring and addressing the real issues in each tourism destination and they should be selected with the participation of the stakeholders. Moreover, this research aims to provide the local government units with the set of indicators to help them come up with their business strategy for the sustainable development of their tourist destination. The research will be conducted in two major destinations in the Philippines: Metro Manila and Baguio City. The target population are the selected stakeholders; the national government – national office of the Department of Tourism and the local tourism office in Baguio City, the private sector, and selected Filipino travellers. The study will use both non-probability sampling techniques which is dependent on the chosen sample frame. A semi-structured personal interview will be conducted and structured mail surveys will be sent to the chosen population, which in this case, are the selected stakeholders. A cross case analysis of the results of the interviews and questionnaires would be done. Identifying their similarities and differences in the results of the data gathering done with the respondents. After the data was gathered and analysed, it has verified the propositions of the study. It has been verified that it is likely that the key indicators on the adoption of a national framework on sustainable tourism development will focus on four areas namely, political implementation of sustainability concepts, environmental performance indicators, social and cultural performance indicators, and economic performance indicators. It is also believed that the adoption of a national framework on sustainability through a set of key indicators will help local government units formulate their own sustainable tourism management plan which will contribute to the sustainability of the tourism development in their tourist destination.